Calcium-/Calmodulin-Dependent Protein Kinase II (CaMKII) Inhibition Induces Learning and Memory Impairment and Apoptosis. (23rd December 2021) - Wang, Jialu; Xu, Xiaoxue; Jia, Wanying; Zhao, Dongyi; Boczek, Tomasz; Gao, Qinghua; Wang, Qianhui; Fu, Yu; He, Miao; Shi, Ruixue; Tong, Xin; Li, Meixuan; et al.
Abstract : Objectives . Inhibition of calcium-/calmodulin- (CaM-) dependent kinase II (CaMKII) is correlated with epilepsy. However, the specific mechanism that underlies learning and memory impairment and neuronal death by CaMKII inhibition remains unclear. Materials and Methods . In this study, KN93, a CaMKII inhibitor, was used to investigate the role of CaMKII during epileptogenesis. We first identified differentially expressed genes (DEGs) in primary cultured hippocampal neurons with or without KN93 treatment using RNA-sequencing. Then, the impairment of learning and memory by KN93-induced CaMKII inhibition was assessed using the Morris water maze test. In addition, Western blotting, immunohistochemistry, and TUNEL staining were performed to determine neuronal death, apoptosis, and the relative signaling pathway. Results . KN93-induced CaMKII inhibition decreased cAMP response element-binding (CREB) protein activity and impaired learning and memory in Wistar and tremor (TRM) rats, an animal model of genetic epilepsy. CaMKII inhibition also induced neuronal death and reactive astrocyte activation in both the Wistar and TRM hippocampi, deregulating mitogen-activated protein kinases. Meanwhile, neuronal death and neuron apoptosis were observed in PC12 and primary cultured hippocampal neurons after exposure to KN93, which was reversed by SP600125, an inhibitor of c-Jun N-terminal kinase (JNK). Conclusions . CaMKII inhibition caused learning and memory impairment and apoptosis, which might be related to dysregulated JNK signaling.